Cover Feature: Interfacial pH Measurements Using a Rotating Ring‐Disc Electrode with a Voltammetric pH Sensor (ChemElectroChem 1/2022). Issue 1 (30th November 2021) - Monteiro, Mariana C. O.; Liu, Xuan; Hagedoorn, Bellenod J. L.; Snabilié, Demi D.; Koper, Marc T. M.
Abstract : The Cover Feature illustrates a Rotating Ring‐Disc Electrode in contact with an electrolyte. In this work, this electrode is functionalized with a pH sensing monolayer and is used to measure the interfacial pH during hydrogen evolution under controlled mass transport conditions. More information can be found in the Article by M C. O. Monteiro, X. Liu et al .